Sustainable Practices in Islamic Education: Implementation and Impact in Traditional Islamic Boarding Schools - Rohman, Muhamad Zulfar; Khotimah, Ilma Husnul (IJIBS, 2024)
Sustainable education has become increasingly crucial in addressing global challenges, particularly those related to environmental degradation. Despite its prominence in academic discourse, its application within Islamic boarding schools (pondok pesantren) remains underexplored, creating a gap that necessitates thorough examination. This study aims to evaluate the implementation of sustainable education within Islamic boarding schools, focusing on supporting and inhibiting factors. Using a qualitative approach, this research employs the CIPP (Context, Input, Process, Product) evaluation model to analyze data collected from interviews, observations, and document reviews. Findings reveal that sustainable education in the context of an Islamic boarding school manifests in three dimensions: intracurricular activities integrating environmental themes into religious education, extracurricular activities such as a Smart Cooking Class, and co-curricular initiatives like the Pancasila Student Profile Strengthening Project (P5). However, challenges persist, including uneven teacher competencies in embedding sustainability values and a narrow focus on specific activities and subjects. The study highlights the need for a broader integration of sustainability principles across disciplines and educational contexts. This research contributes to the field by providing a nuanced understanding of sustainable education implementation in Islamic boarding schools and offers recommendations for enhancing its scope and effectiveness in similar educational settings.